Evaluation of in vitro Cytotoxic Effects of Especifico Pessoa Phytotherapic Tincture on Ehrlich Tumor Cells and Mice Spleen Cells - Castoldi, Lindsey [UNESP]; Albiero, Lucinéia Reuse; Nery, Eduardo Figueredo; Kelly, Taiany Oliveira; Silva Dalazen, Jeniffer Charlene; Masochini, Rosângela Guerino (Fronteiras: Journal of Social, Technological and Environmental Science, 2020)
Especifico Pessoa (EP) is traditionally used for the treatment of snakebite envenoming. The traditional use of EP and its properties have been reported. In this study, we evaluated the in vitro cytotoxic effects of EP on Ehrlich tumor and mice spleen cells. Cytotoxicity assay was carried out by using Trypan blue exclusion method. Spleen cell suspension was prepared (n=2) with RPMI medium and tumor cell suspension was prepared from ascitic fluid of Ehrlich tumor-bearing mice (n=1); both the suspensions contained 4 x 106 cells mL-1. Pure EP or EP diluted in RPMI (1:2; 1:4) was used. The results were expressed as percentage of cell viability and demonstrate that EP is toxic to Ehrlich cells at all concentrations (Control: 96.42 ± 3.40; Pure: 1.55 ± 2.91; 1:2: 4.85 ± 5.04; 1:4: 13.39 ± 5.08), but nontoxic to spleen cells in at the lowest dilution (Control: 72.86 ± 13.79; Pure: 13.52 ± 6,36; 1:2: 41.36 ± 13.51; 1:4: 56.59 ± 8.62). Therefore, the results demonstrate that EP has cytotoxic effects, depending on the dose and the cell line evaluated.
Avaliação da Citotoxicidade in vitro da Tintura Fitoterápica Especifico Pessoa sobre Células do Tumor de Ehrlich e sobre Células Esplênicas de Camundongo
Keywords: Cytotoxicity; Ehrlich Tumor; Especifico Pessoa; Phytotherapic